Evaluasi K3 di Pabrik Gula Rejoso Berdasarkan UU No. 13/2003 - Andrian Wijaya; Romi Faslah (CV. ITTC INDONESIA, 2025)
This study explores the implementation of occupational safety and health (OSH) standards at PT Rejoso Manis Indo, Blitar Regency, based on Law Number 13 of 2003 concerning Manpower. It focuses on the enforcement of Articles 86 and 87, which require companies to protect workers through integrated safety management systems. The research uses observation, interviews, and document analysis to examine company policies and worker experiences. Findings show that the company has provided personal protective equipment (PPE), ventilation, and health facilities. However, issues remain, including poor PPE quality, lack of compliance by workers, and inefficient machinery layout. Despite these shortcomings, the company fulfills its responsibilities by offering medical coverage, wages during recovery, and accident insurance through BPJS. Workers have responded positively to the protection provided. Nonetheless, ongoing improvements in safety training, supervision, and equipment maintenance are necessary. The study concludes that while the company complies with the law in principle, full implementation of OSH requires stronger enforcement and cultural shifts in workplace behavior. This research contributes to understanding how labor law is applied in the industrial sector and underscores the importance of building a safe and productive work environment.